Neuroactive Steroids Reverse Tonic Inhibitory Deficits in Fragile X Syndrome Mouse Model - Modgil, Amit; Vien, Thuy N.; Ackley, Michael A.; Doherty, James J.; Moss, Stephen J.; Davies, Paul A. (Frontiers in Molecular Neuroscience, 2019)
Fragile X syndrome (FXS) is the most common form of inherited intellectual disability. A reduction in neuronal inhibition mediated by γ-aminobutyric acid type A receptors (GABAARs) has been implicated in the pathophysiology of FXS. Neuroactive steroids (NASs) are known allosteric modulators of GABAAR channel function, but recent studies from our laboratory have revealed that NASs also exert persistent metabotropic effects on the efficacy of tonic inhibition by increasing the PKC-mediated phosphorylation of the α4 and β3 subunits which increase the membrane expression and boosts tonic inhibition. We have assessed the GABAergic signaling in the hippocampus of FMRP knock-out (Fmr1 KO) mouse. The GABAergic tonic current in dentate gyrus granule cells (DGGCs) from 3-5 week old (p21-35) Fmr1 KO mice was significantly reduced compared to WT mice. Additionally, spontaneous inhibitory post synaptic inhibitory current (sIPSC) amplitudes were increased in DGGCs from Fmr1 KO mice. While sIPSCs decay in both genotypes was prolonged by the prototypic benzodiazepine diazepam, those in Frm1-KO mice were selectively potentiated by RO15-4513. Consistent with this altered pharmacology, modifications in the expression levels and phosphorylation of receptor GABAAR subtypes that mediate tonic inhibition were seen in Fmr1 KO mice. Significantly, exposure to NASs induced a sustained elevation in tonic current in Fmr1 KO mice which was prevented with PKC inhibition. Likewise, exposure reduced elevated membrane excitability seen in the mutant mice. Collectively, our results suggest that NAS act to reverse the deficits of tonic inhibition seen in FXS, and thereby reduce aberrant neuronal hyperexcitability seen in this disorder.